Chemistry and sources of PM2.5 and volatile organic compounds breathed inside urban commuting and tourist buses. (15th February 2020) - Fernández-Iriarte, Amaia; Amato, Fulvio; Moreno, Natalia; Pacitto, Antonio; Reche, Cristina; Marco, Esther; Grimalt, Joan O.; Querol, Xavier; Moreno, Teresa
Abstract: Inhalable particulate matter (size <2.5 μm: PM2.5 ) inside commuting and tourist buses moving through the city of Barcelona, Spain, was chemically analysed. The analyses show PM dominated by organic carbon (mostly 10–20 μg/m 3 ) and elemental carbon (mostly 3–6 μg/m 3 ; OC/EC = 3.4), followed by SO4 2, Fe, Ca, K, Al2 O3, Mg, and Na, with calculated mineral content being around one third that of total carbon. Elemental carbon levels are higher inside diesel buses than those powered by natural gas or electricity, and higher in the upper floor of open-top double decker tourist buses than in the lower floor. Overall, major element concentrations inside the buses are typically 2–8 times higher than 24 h-averaged urban background levels, although some metallic trace elements, notably Cu and Sb, are exceptionally enriched due to the presence of brake particles, especially on routes involving higher gradients and therefore more brake use. In contrast, Cu and Sb concentrations in electric buses are unexceptional, presumably because these buses rely more on regenerative braking and are hermetically sealed when moving. Seasonal differences reveal PM to be more mineral in winter (Al2 O3 1.3 μg/m 3 vs. summer average of 0.3 μg/m 3 ), with summer enrichment in Na, Mg, P, V, Ni and SO4 2− being attributed to marine aerosols contaminated by port emissions. Source apportionment calculations identify 6 main factors: road dust resuspension, metalliferous (brake wear and metallurgy), local urban dust, secondary sulphate and shipping (6%), vehicle exhaust (19%), and an indoor source (46%) interpreted as likely related to the textile fibres and skin flakes of bus occupants. Volatile Organic Compounds measured inside all buses except one were dominated by 2-Methylpentane (14–36 μg/m 3 ), Toluene (10–30 μg/m 3 ), Xylene isomers (10–28 μg/m 3, with m- » o- > p-Xylene) and n-Pentane (5–15 μg/m 3 ). ƩBTEX concentrations were <70 μg/m 3, with Toluene being commonest, followed by m-Xylene, with p-Xylene, o-Xylene and Ethylbenzene each below 7 μg/m 3 and Benzene concentrations always less than the EU limit value of 5 μg/m 3 . The VOCs mixture is similar to that recently reported from inside Barcelona taxis (although inside the larger volume bus VOC concentrations are lower than in the taxis) and is interpreted as providing a chemical fingerprint characterising traffic-contaminated ambient air in the city road environment. The notable exception to the VOC content was a brand new hybrid diesel bus still offgassing volatiles to such an extent that Ʃ(alkane + alkene + aromatic) indoor concentrations exceeded 800 μg/m 3, with ƩBTEX ten times higher than normal. Highlights: Interior bus air chemistry can be influenced both by route taken and bus model. Carbon and most metal concentrations are much higher in buses than urban background. Enhanced levels of Cu and Sb are attributed to brake particles entering the bus. Inhalable PM are mostly textile fibres, skin flakes, vehicle exhaust and brake wear. New buses show much higher VOC signature due to off-gassing of interior materials.